Mobile Technology: Teaching Opportunities, Analysis and Research - Khujakulov Sherzod Amankulovich (International Journal on Integrated Education, 2022)
This article focuses on the content, advantages and peculiarities of teaching on the basis of mobile technologies, one of the promising areas of Education. There is also an analysis of mobile teaching and its types, views on a number of studies conducted, as well as the use of the internet and mobile devices.